Humidity sensitivity of topas optical fibre bragg grating - Bang, Ole; Yuan, Wu; Khan, Lutful; Webb, David J.; Johnson, Ian P.; Stefani, Alessio; Nielsen, Kristian; Rasmussen, Henrik Koblitz; Kalli, Kyriacos (My University, 2011)
Fibre Bragg gratings at 1568nm have been inscribed in single mode TOPAS microstructured polymer optical fibre to characterise thermal and humidity sensitivity of the fibres in the 1550nm spectral region. Results demonstrate a temperature sensitivity of approximately -36 pm/C and a humidity sensitivity of no more than - 0.59 pm/%RH. The fibre material appears to be very attractive for long term monitoring of high strains because of its insensitivity to humidity.
Keywords: Fibre Bragg grating sensors; High strains; Humidity sensitivity; Long term monitoring; Polymer optical fibre; Spectral region; Temperature sensitivity; TOPAS; Fiber optic sensors; Humidity sensors; Plastic optical fibers; Fiber Bragg gratings